PENGARUH MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE (IOC) TERHADAP KEAKTIFAN BELAJAR DAN PEMAHAMAN SISWA PADA MATA PELAJARAN IPS DI KELAS IV SDN 4 SANTONG - Cahyani, Annisa; Husni, Muhammad; Burhanuddin, Burhanuddin (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine the effect of the Inside Outside Circle (IOC) learning model on students’ learning activeness and understanding in Social Studies (IPS) in fourth grade at SDN 4 Santong. This research employed an experimental method using a pretest–posttest non-equivalent control group design. The population consisted of all 27 fourth-grade students. Data were analyzed using a t-test. The hypothesis testing results showed that the pretest significance value was 0.315 > 0.05, indicating no significant difference between the experimental and control groups before treatment. However, the posttest results showed a significance value of 0.003 < 0.05, indicating a significant difference between the two groups after the implementation of the learning model. These findings demonstrate that the use of the Inside Outside Circle (IOC) learning model has a significant effect on improving students’ learning activeness and understanding in Social Studies. In conclusion, the IOC learning model is effective in enhancing both student engagement and comprehension in elementary school Social Studies learning.